VD_FINDINFO HC / 2011 / 125 vom 18. Januar 2011 - VD Tribunal cantonal (2011)
EXPULSION DE LOCATAIRE, RETRAITVOIE DE DROIT, DÉPENS | 257d al. 1 CO, 160 al. 1 CPC, 162 al. 1 CPC, 94 al. 1 CPC, 29 LPEBL